Impact of proximity from chemical and pharmaceutical universities on startup founding: empirical evidence from the Visegrad countries - Melinda Krankovits; Petra Kinga Kézai; Áron Szennay (Discover Sustainability)
Abstract This paper examines the spatial distribution of chemical startups in the Visegrad Countries (Czech Republic, Slovakia, Poland, and Hungary), highlighting their potential to drive technological innovation by creating new products or services under conditions of high uncertainty. The study focuses on the proximity of these startups to medical or chemical universities and those with biotechnological research fields to better understand their geographical patterns and potential knowledge spillovers. Data were drawn from Crunchbase, a comprehensive startup database, resulting in a final sample of approximately 333 operational chemical, pharmaceutical, or biotechnological startups. Companies were identified using keyword-based searches, while startup locations and distances to the nearest medical universities were recorded. Statistical methods were applied to assess spatial patterns. Results indicate that these startups are frequently located in cities with biotechnological, chemical, or medical universities. Our findings highlight different types of startup activities and levels of financial support across the Visegrad countries, emphasising the role of chemical startups in fostering technological advancement and sustainable development.